2017
DOI: 10.1111/jfbc.12452
|View full text |Cite
|
Sign up to set email alerts
|

Seed extracts from Myristica fragrans (Nutmeg) and Moringa oleifera (Drumstick tree) inhibits enzymes relevant to erectile dysfunction and metal-induced oxidative damage in rats' penile tissues

Abstract: This study evaluated the effects of nutmeg and drumstick seed extracts on enzymes (phosphodies- constituents. These findings demonstrate that the studied seeds could be explored as an alternative remedy for the management of ED. However, the seed of nutmeg was more effective than drum stick.terase Practical applicationsNutmeg and Drumstick seeds are commonly consumed medicinal seeds and are a potential source of polyphenols with strong antioxidant activity. They are used as functional foods and could serve as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 49 publications
(60 reference statements)
1
20
0
Order By: Relevance
“…This is because inhibition of arginase activity could give way to the increase NO bioavailability, which in turn could induce smooth muscle relaxation, and thereby enhances penile rigidity (Sakai et al, ). The result of the studied seed extracts on arginase activity, coincides with the reports of Odubanjo et al () where extracts from the seed of Myristica fragrans (Nutmeg) and Moringa oleifera (Drumstick tree) inhibited arginase activity, the effect that was attributed to the polyphenol compounds. Flavonoid has been reported to be potent inhibitors of arginase activity, via hydrophobic interactions with the active site of the arginase.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This is because inhibition of arginase activity could give way to the increase NO bioavailability, which in turn could induce smooth muscle relaxation, and thereby enhances penile rigidity (Sakai et al, ). The result of the studied seed extracts on arginase activity, coincides with the reports of Odubanjo et al () where extracts from the seed of Myristica fragrans (Nutmeg) and Moringa oleifera (Drumstick tree) inhibited arginase activity, the effect that was attributed to the polyphenol compounds. Flavonoid has been reported to be potent inhibitors of arginase activity, via hydrophobic interactions with the active site of the arginase.…”
Section: Resultssupporting
confidence: 90%
“…The PDE-5 activity was determined using the method of Kelly and Butler (1977) as described by Odubanjo, Olasehinde, Oyeleye, Oboh, and Boligon (2018). Rats were anesthetized and sacrificed, and the penile tissue was carefully removed, rinsed with 0.1 M Tris-HCl buffer containing 1 mM CaCl 2 and 50 mM NaCl (pH 8.0), and homogenized in cold buffer.…”
Section: Enzymes (Pde-5 Arginase Ache and Ace) Inhibition Assaysmentioning
confidence: 99%
“…Oxidative stress damage the neuronal cells, impair communication flow and cognitive function (Adefegha et al, ; Ademosun et al, ; Nwanna et al, ). Hence, consumption of phenolic‐rich compound could augment body's antioxidant status, via scavenging of radical and metal chelation, which could be a strategic means of attenuating oxidative stress in neurodegenerative conditions (Ayala, Muñoz, & Argüelles, ; Odubanjo, Olasehinde, Oyeleye, Oboh, & Boligon, ). The extracts from QU and SA scavenged DPPH and hydroxyl radicals, and also chelate Fe 2+ in a dose‐dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…The compounds were extracted effectively in the solvents in the order of acetone>ethanol>aqueous. Also studies by [6] showed that nutmeg seeds exhibited strong inhibitory effects and that the effects exhibited by nutmeg may be linked to high phenolic and flavonoid contents.…”
Section: Resultsmentioning
confidence: 99%